The Effectiveness of Mung Beans and Katuk Leaves on Increasing Hemoglobin Levels in Maternity at TPMB Rennie Yuwitasari in 2022 - Rennie Yuwitasari; Nursitiyaroh Nursitiyaroh; Budi Ermanto (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background : An iron-rich protein called hemoglobin has an affinity for oxygen, which causes it to produce oxyhemoglobin in red blood cells. O2 (oxygen) will be transported from the lungs to the body's tissues as a result of this function. Purpose of Writing: to determine the Effectiveness of Mung Beans and Katuk Leaves on Increased Hemoglobin Levels in Mothers Giving Birth at TPMB Rennie Yuwitasari Year 2022”. Research Method : This research is an experiment designed One – group pre test – post test design. A sample of 15 people with a quantitative approach. The study population was 20 postpartum mothers who attended TPMB Rennie Yuwitasari. The sampling method used consisted of a total sample of 20 people who were divided into two groups, namely 10 groups receiving green beans and 10 groups receiving katuk leaves. The sampling technique used was accidental sampling. Research results: It is known that the Hb assessment before giving katuk leaves obtained an average value of 10.300 and a standard deviation of 0.7832 with a minimum Hb rating of 8.8 and a maximum of 11.4 while after giving katuk leaves , the mean value was 11.230, with a standard deviation of 0.5877, and the Hb value ranged from 9.8 to 12.0. We got Asimp. The Sig (2-Sided) value is 0.169, and because 0.169 > 0.05 the hypothesis is not proven. This means that there is no difference in giving katuk leaves or green beans to increase hemoglobin levels. So that it can be concluded that bivariate data analysis, namely green beans and katuk leaves have the same effectiveness value in increasing Hb levels in postpartum mothers at TPMB Rennie Yuwitasari. Conclusions and Suggestions: The findings of this study are expected to increase postpartum mothers' understanding of increasing Hb levels by consuming green beans and katuk leaves which have been proven to increase Hb levels.